Mediators of physical activity change in a behavioral modification program for type 2 diabetes patients - Van Dyck, Delfien; De Greef, Karlijn; Deforche, Benedicte; Ruige, Johannes; Tudor-Locke, Catrine E; Kaufman, Jean-Marc; Owen, Neville; De Bourdeaudhuij, Ilse (The international journal of behavioral nutrition and physical activity, 2011)
Many studies have reported significant behavioral impact of physical activity interventions. However, few have examined changes in potential mediators of change preceding behavioral changes, resulting in a lack of information concerning how the intervention worked. Our purpose was to examine mediation effects of changes in psychosocial variables on changes in physical activity in type 2 diabetes patients. Ninety-two patients (62 ± 9 years, 30, 0 ± 2.5 kg/m(2), 69% males) participated in a randomized controlled trial. The 24-week intervention was based on social-cognitive constructs and consisted of a face-to-face session, telephone follow-ups, and the use of a pedometer. Social-cognitive variables and physical activity (device-based and self-reported) were collected at baseline, after the 24-week intervention and at one year post-baseline. PA was measured by pedometer, accelerometer and questionnaire. Post-intervention physical activity changes were mediated by coping with relapse, changes in social norm, and social modeling from family members (p ≤ 0.05). One-year physical activity changes were mediated by coping with relapse, changes in social support from family and self-efficacy towards physical activity barriers (p ≤ 0.05) For patients with type 2 diabetes, initiatives to increase their physical activity could usefully focus on strategies for resuming regular patterns of activity, on engaging family social support and on building confidence about dealing with actual and perceived barriers to activity. NCT00903500, ClinicalTrials.gov.